The Transcriptomic Landscape of Mismatch Repair-Deficient Intestinal Stem Cells - Bommi, Prashant V; Bowen, Charles M; Reyes-Uribe, Laura; Wu, Wenhui; Katayama, Hiroyuki; Rocha, Pedro; Parra, Edwin R; Francisco-Cruz, Alejandro; Ozcan, Zuhal; Tosti, Elena; Willis, Jason A; Wu, Hong; et al. (Cancer research (Chicago, Ill.), 2021)
Lynch syndrome is the most common cause of hereditary colorectal cancer and is secondary to germline alterations in one of four DNA mismatch repair (MMR) genes. Here we aimed to provide novel insights into the initiation of MMR-deficient (MMRd) colorectal carcinogenesis by characterizing the expression profile of MMRd intestinal stem cells (ISC). A tissue-specific MMRd mouse model (Villin-Cre;Msh2 ) was crossed with a reporter mouse ( ) to trace and isolate ISCs (Lgr5+) using flow cytometry. Three different ISC genotypes ( -KO, -HET, and -WT) were isolated and processed for mRNA-seq and mass spectrometry, followed by bioinformatic analyses to identify expression signatures of complete MMRd and haplo-insufficiency. These findings were validated using qRT-PCR, IHC, and whole transcriptomic sequencing in mouse tissues, organoids, and a cohort of human samples, including normal colorectal mucosa, premalignant lesions, and early-stage colorectal cancers from patients with Lynch syndrome and patients with familial adenomatous polyposis (FAP) as controls. -KO ISCs clustered together with differentiated intestinal epithelial cells from all genotypes. Gene-set enrichment analysis indicated inhibition of replication, cell-cycle progression, and the Wnt pathway and activation of epithelial signaling and immune reaction. An expression signature derived from MMRd ISCs successfully distinguished MMRd neoplastic lesions of patients with Lynch syndrome from FAP controls. SPP1 was specifically upregulated in MMRd ISCs and colocalized with LGR5 in Lynch syndrome colorectal premalignant lesions and tumors. These results show that expression signatures of MMRd ISC recapitulate the initial steps of Lynch syndrome carcinogenesis and have the potential to unveil novel biomarkers of early cancer initiation. SIGNIFICANCE: The transcriptomic and proteomic profile of MMR-deficient intestinal stem cells displays a unique set of genes with potential roles as biomarkers of cancer initiation and early progression.